PERLINDUNGAN HUKUM TERHADAP PEMBELI APARTEMEN ATAS TINDAKAN WANPRESTASI PENGEMBANG - Muntiasih Muntiasih (President University, 2016)
Based on Law Number 20 of 2011 concerning Flats, the marketing of flats has been carried out before the construction of flats is carried out. Such sale and purchase of apartment units is done by ordering in advance the unit to be purchased, then poured in the preliminary agreement in the form of an order confirmation proof which is then registered with the Notary (Waarmerking) office. So when construction of flats began, there were already many consumers who bought the apartment. The author in this thesis wants to examine and analyze further whether the Flats Booking Confirmation waarmerking can provide legal certainty for consumers and how is the form of legal protection for consumers if the developer defaults before the Sale and Purchase Agreement is made. The research method used is normative legal research, namely legal research conducted by examining library materials or secondary legal material while in searching for and collecting data is done with two approaches, namely the legal approach and the conceptual approach.The results of the study show that the apartment booking confirmation letter made by the developer and waarmerking by a Notary has the power of proof as long as the parties acknowledge it or there is no denial from either party or in other words have imperfect proof power. If the order confirmation letter for the flats is used as evidence, then in the evidence in the court, later it will require other evidence and witnesses to prove the truth. In the sale and purchase of flats between developers and consumers, the developer's responsibility can be seen since the issuance of brochure flats offering by developers. Brochures issued by the developer can also be used as a basis for claims for consumers who feel disadvantaged because of the lack of facilities promised in the brochure.